EDUCATION AND EMANCIPATION IN THE HORIZON OF ILLUMINISM (Cadernos de Ética e Filosofia Política, 2015)
volume is a critical and historical reflection on the named “crisis of education”. To understand the roots of this issue, the author investigates the Modern bases of the relation of education with emancipation in times of Enlightenment. The paper presents two movements: (a) an inquiry on Illuminist principles of Modern education by the pedagogical trends of their proposals as well as their newness, to know: the emancipatory meaning of Modern project is no more structured by the apprehension of a general culture, but in sense of developing the people as a citizen in equal terms and the criticism against all authoritarian tutelage in defense of autonomy. Then, transformation in spite of bildung; (b) from this genesis of Modern education, Pujol returns to the debate on crisis of education and questions: to what extent the Illuminist project of emancipation does not causes new forms of subjection, which avoids the physical authority but sustains a new authority of the laws? To what extent the crisis of education contains a critical perspective against this Illuminist heritage, expressed by the perspective of many young people, who conceives school as an institution of tutelage? Could we reverse the Illuminist emancipatory project, constituting a “counter-emancipation” independent of all models of authority and tutelage?